2020
DOI: 10.1024/0301-1526/a000839
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1 (PAI-1) 4G/5G promoter polymorphisms and risk of venous thromboembolism – a meta-analysis and systematic review

Abstract: Summary: Background: A 4G/5G polymorphism in the promoter region of the plasminogen activator inhibitor type 1 (PAI-1) gene has been reported to enhance the plasma levels of PAI-1, which plays an important role in fibrinolysis disorders and venous thromboembolism, but a large number of studies have reported inconclusive results. Therefore, we performed a meta-analysis to analysis these associations. Materials and methods: We performed a publication search for articles published before April 2019 by using the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 27 publications
2
76
0
2
Order By: Relevance
“…[ 22 ] According to the evaluation content of Newcastle-Ottawa scale scale, they were divided into 8 items and 9 points, and each score was 1 point. [ 23 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 22 ] According to the evaluation content of Newcastle-Ottawa scale scale, they were divided into 8 items and 9 points, and each score was 1 point. [ 23 ]…”
Section: Methodsmentioning
confidence: 99%
“…The PAI-1 levels in the 4G/4G genotype were estimated to be approximately 25% higher than those in the 5G/5G genotype. 18 PAI-1 gene 4G/5G polymorphism is associated with many diseases, including venous thromboembolism, 5,19 polycystic ovary syndrome, 14 asthma, 20 myocardial infarction, 21 and LV. Some LV patients were successfully treated with tPA therapy, and sequencing results revealed that their PAI-1 genotypes were homozygous (4G/4G).…”
Section: Pai-1 4g/5g Gene Polymorphismmentioning
confidence: 99%
“…PAI-1 4G/5G gene polymorphism and elevated plasma levels of PAI-1 have been detected in venous thromboembolism, and PAI-1 may be a suitable biomarker for assessing the risk of venous thromboembolism. 5 In recent years, Agirbasli et al observed that increased mRNA expression of PAI-1 in cutaneous lesions of LV was highly associated with histological findings of ulcers. 6 Moreover, LV patients with PAI-1 promoter homozygosity (4G/4G) responded well to tissue plasminogen activator infusion therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The genotypes of this gene polymorphism are 4G4G, 4G5G, and 5G5G respectively, which regulate the expression level of PAI-1. 23,24 Abundant existing studies have confirmed that genotype 4G4G is related to the increase in PAI-I gene transcription. [25][26][27] As such, it is reason able to suppose that the plasma PAI-1 level is the highest in genotype 4G4G, which is followed by genotype 4G5G, and is the lowest in genotype 5G5G.…”
Section: Introductionmentioning
confidence: 99%